PROBLEMS IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) IN HIGHER EDUCATION (Universitas Islam Negeri Sunan Ampel Surabaya, 2014)
English for Specific Purpose appeared due to the awareness that general English course was not suitable for the learners’ need, especially in higher education. In the teaching of ESP, the materials are focused on the learners’ needs or their specific fields of study and it is assumed that they have basic language skills of general English. The purpose of this study was to analyze the problems that arise in teaching English for Specific Purpose (ESP) in higher education. The writer investigated the problems and the causes by reading many literature reviews related to the topic. The findings showed that there are five main problems in ESP. They are related to (1) teaching pedagogy, (2) the teachers ,(3) the design of the course, (4) students’ ability and (5) students’ needs. Some suggestions are also given to solve the problems in teaching English for Specific Purpose in higher education.